Environmental Mechanisms and Corporate Values: The Role of Size Moderation in Indonesian High-Profile Companies - Rifa Maulina Syaharani; Edy Anan (CV Edujavare Publishing, 2026)
This study aims to analyze the influence of green accounting, carbon emission disclosure, and carbon tax on company value and test the role of company size as a moderation variable in high-profile companies listed on the Indonesia Stock Exchange. The study used a quantitative approach with balanced panel data covering 10 companies in the consumer non-cyclicals, basic materials, industrials, and energy sectors during the period 2020–2024 (50 company-year observations). Company value is measured using Tobin's Q, green accounting is proxied through the ratio of environmental costs to revenue, carbon emissions disclosure through emission intensity, carbon tax through the ratio of carbon cost exposure to revenue, while company size is measured using the natural logarithm of total assets. Debt to Equity Ratio and Return on Assets are used as control variables. The analysis was carried out using the Random Effect Model on EViews 12 after going through the Chow, Hausman, and Lagrange Multiplier tests. The results of the study show that green accounting and carbon emission disclosure do not have a significant effect on the company's value at a significance level of 5%, while the carbon tax has a marginally negative effect at the level of 10%. Moderation testing shows that company size significantly moderates the relationship between green accounting, carbon emissions disclosure, and carbon taxes on company value. The entire interaction coefficient has the opposite direction to the main coefficient, indicating that the larger the size of the company, the weaker the influence of environmental information on the company's value. In addition, the Adjusted R² value increased from 9.58% to 55.15% after including the moderation variable, indicating an improvement in the model's ability to explain variations in the company's value. This study expands the environmental accounting literature by showing that company size is not just a control variable, but a contextual factor that determines how the market responds to environmental information. These findings provide implications for companies to substantively improve the quality of environmental reporting, for investors to consider company size in investment decision-making, and for regulators to develop more uniform sustainability reporting standards.